24.8k views
1 vote
Simplify the expression when y = 6: 4y + (7 x 2) -13

User Ssss Ppppp
by
5.8k points

2 Answers

3 votes

Answer:

25

Explanation:

So we first simply 4y+(7 times 2)-13

=4y+1

Then we put y=6 in!

24+1

=25

Hoped I helped!

Me and Eternalvanimelda27 are the same person, so we are going to have the same explanation!!!

User Arikon
by
6.4k points
5 votes

Answer:

25

Explanation:

So we first simply 4y+(7 times 2)-13

=4y+1

Then we put y=6 in!

24+1

=25

Hoped I helped!

Me and Vanimeldawolf29 is the same person, so we are going to have the same explanation!!!

User Prashant Kadam
by
6.1k points